2016
DOI: 10.1111/ijpp.12256
|View full text |Cite
|
Sign up to set email alerts
|

Provision of travel medicine advice through community pharmacies: assessment of knowledge, attitudes and practices of pharmacists in Malaysia

Abstract: There are gaps in the knowledge and practice of travel medicine among Malaysian pharmacists. Positive attitudes of pharmacists towards travel medicine and appropriate interventions, such as incorporation of travel medicine in local pharmacy curricula, continuous pharmacy education or certified training may improve the quality of travel advice given and allow pharmacists to be recognised as a credible source of information on travel medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Indeed, a striking finding depicted that less than a quarter of participants seemed knowledgeable about the seven more frequent infectious diseases related to travel, with a total mean score of knowledge of 2.9. The finding that respondents had a lack of knowledge is in accordance with previous reports, which have shown that community pharmacists have a knowledge gap and low confidence in providing this type of care [15,23]. This fact emphasizes the importance that pharmacists should be informed since their level of awareness should primarily be improved.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, a striking finding depicted that less than a quarter of participants seemed knowledgeable about the seven more frequent infectious diseases related to travel, with a total mean score of knowledge of 2.9. The finding that respondents had a lack of knowledge is in accordance with previous reports, which have shown that community pharmacists have a knowledge gap and low confidence in providing this type of care [15,23]. This fact emphasizes the importance that pharmacists should be informed since their level of awareness should primarily be improved.…”
Section: Discussionsupporting
confidence: 90%
“…Several investigations on the knowledge, attitudes, and behavior of the general population and physicians regarding travel medicine have been conducted in different countries [4][5][6], and, to date, there is also research on the involvement of community pharmacists in this field [7][8][9][10][11][12][13][14][15][16]. This is of utmost importance in order to provide important information for planning training interventions targeted towards these professionals to positively affect travelers' health.…”
Section: Introductionmentioning
confidence: 99%
“…The included studies are presented in Additional file 1, which shows pharmacists' awareness, perceptions, or attitudes toward various extended pharmacy services and drive-thru service at community setting including: extended role services [35], pharmaceutical care services [36][37][38][39][40][41][42][43][44], over-the-counter pharmaceutical services [45,46], health promotion and health education [47], public health activities [48,49], value-added services [50], minor aliment services [51], medication reconciliation [52], professional services [53,54], services for people with mental disorders [55][56][57], lifestyle assistance services for people with cardiovascular diseases [58], anticoagulation management services [59], services for geriatrics [60], osteoporosis assessment screening [61], back pain management services [62], Human Papillomavirus (HPV) Vaccination Services [63], emergency contraception services [64], clinical services [65], intermediate care services [66,67], interactions with general practitioners [68], oral health services [69,70] [71,72], travel medicine services [73], smoking cessation counselling [74,<...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…To satisfy the demands of public health, pharmacists are seeking to increase their power inside the healthcare system. As an example, some pharmacists are starting to advise patients on travel medicine and monitor blood pressure readings in an outpatient setting [67,69]. Additionally, the most beneficial service offered by neighborhood pharmacists is counseling [83].…”
Section: Abu-farha Et Al (2022) -Jordanmentioning
confidence: 99%